Audio video system in Filipino residences - Fortinez, Jp E.; Mayo Adelaida V. (1998.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Home video system